The Role of Parents in Guiding Children in Online Learning in the RT 2/ RW4 Environment of Malanu Village - marlinda indah eka budiarti; Feronika Yekwan (THEOREMA: The Journal Education of Mathematics, 2022)
This study aims to see how the role of parents in terms of learning assistance during Covid 19. The method used is field research (FieldReseach), that is, if this research departs directly into the field to make direct observations about the role of parents towards children in online learning that is carried out from the student's home or environment. The research location is in RT 2/RW 4, Malanu Village, Sorong City. The data collection techniques used were questionnaires and interviews with parents of students. The results of this study indicate that 6 parents have tried to be able to take the time to be able to help and accompany their children's learning activities directly. While the other 4 parents have tried, even though they have not been able to maximize it. The several inhibiting factors are 1) external factors and, 2) internal factors.